If the BIT Fits: The Proposed Bilateral Investment Treaty between the United States and the People’s Republic of China - Steinert, Timothy A. (Columbia Journal of Asian Law, 1988)
Since the normalization of relations between the People’s Republic of China (PRC) and the United States in 1979, the two governments have conducted a number of bilateral negotiations aimed at establishing closer economic ties and greater mutual understanding. These negotiations have yielded several trade and investment-related agreements including a bilateral trade agreement, several bilateral income tax agreements, and a bilateral investment guarantee agreement. However, after five years of intermittent negotiations, the two sides have yet to come to terms on a bilateral investment treaty (BIT).